Chemical inactivity of GaN(0001) surface – The role of oxygen adsorption – Ab initio picture. (1st March 2019) - Kempisty, Pawel; Strak, Paweł; Sakowski, Konrad; Krukowski, Stanisław
Abstract: Density Functional Theory (DFT) calculations were used to determine adsorption of oxygen at GaN(0001), i.e. Ga-terminated surface. It was shown that at low coverage the oxygen molecule dissociates during adsorption so that the two separate O adatoms are located in H3 sites. Oxygen adatom saturates three Ga broken bonds, modifying their energy by overlap with Op states, so that the three states are degenerate with valence band (VB). The electron counting rule (ECR) indicate on the electron surplus, the excess electrons are donated to other Ga broken bond states, the adsorption energy is equal to 3.74 eV/atom for clean surface. At the first critical coverage θ O = 5 16 ML, the Fermi level is shifted to conduction band while at the second critical coverage θ O = 3 8 ML it is shifted down to VBM. The adsorption energy is Δ E 1 2 O 2 ( N ) = − 3.67 eV for θ O ≤ 7 24 ML, for θ O = 15 48 ML and θ O = 16 48 ML decreases Δ E 1 2 O 2 ( N ) = − 3.51 eV and Δ E 1 2 O 2 ( N ) = − 3.31 eV, respectively, for θ O = 17 48 the energy jumps to Δ E 1 2 O 2 ( N ) = − 3.60 eV, and for higher coverage θ O ≥ 3 8 the energy rapidly decreases to zero and becomes negative The singular point at θ O = 17 48 ML is essential for stability of oxygen coverage of the surface. The equilibrium pressure at low coverage is 10 −5 bar for 1500 K and 10 −12 bar 1000 K. It is reduced for higher coverage, due to reduction of the energy and configurational entropy contributions. At the coverage θ O = 17 48 ML the pressure is reduced by several orders of magnitude, indicating extremely high thermodynamic stability of such coverage, which is responsible for chemical inactivity of GaN(0001) surface observed in experiments, the critical factor for mechano-chemical polishing of the substrates for electronic applications.